RASIO PROFITABILITAS, LIKUIDITAS, DAN SOLVABILITAS TERHADAP HARGA SAHAM (PERUSAHAAN KELAPA SAWIT YANG TERDAFTAR DI BEI) - Satria Dwiyana, Fernando Yogha; Ni, Sriwinarti Ketut; Defel, Septian (Institut Agama Hindu Negeri Gde Pudja Mataram, 2024)
Oil palm is one of the plants that can produce oil for commercial use (Fuadah, 2018). Palm oil can also be seen as a form of progress in national development. Apart from opening up employment opportunities, another important contribution is its role as a source of foreign exchange for the country. Global demand for palm oil tends to increase from 2016 to 2020.The subject of this study focuses on palm oil companies registered on the BEI from 2018 to 2022. This research is quantitative in nature. The sample for this study was determined using a purposive sampling technique, resulting in 12 samples and 60 observation data points. Secondary data in this research was obtained from the website (BEI) and websites of related companies. This research uses multiple linear regression analysis as a method for analyzing data.Based on the results of the return on equity (ROE) variable, the Sig. is 0.009, then the conclusion is accepted. Based on the results of the variable current ratio (CR), the Sig. is 0.009, then the conclusion is accepted. Based on the results of the variable debt to equity ratio (DER) value Sig. is 0.301, then the result is rejected.Referring to this, it can be stated that: the current ratio (CR) and return on equity (ROE) variables have an influence on share prices, while the debt to equity ratio (DER) has no influence on share prices.